2006
DOI: 10.1136/vr.159.15.485
|View full text |Cite
|
Sign up to set email alerts
|

Metallic foreign bodies in the tongues of 16 horses

Abstract: The history, clinical signs, results of diagnostic imaging, treatment methods and outcome of 16 adult horses with a metallic foreign body in the tongue are reviewed. All the horses had a swollen tongue, they salivated excessively and were partially to completely anorexic. Less common clinical signs were fever, an enlarged and painful intermandibular space, dysphagia, unilateral tongue paralysis and halitosis. Most of the horses had shown clinical signs for less than 24 hours. The foreign bodies were diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 2 publications
0
45
1
3
Order By: Relevance
“…A previous study found metallic wires (4 to 12 cm in length) in the tongues of 16 horses, but the authors did not report whether the lower alimentary tract was also affected (Pusterla and others 2006). In the present study, the upper alimentary tract was unaffected by metallic wires of similar length (4 to 8 cm in length) that affected the lower alimentary tract only.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study found metallic wires (4 to 12 cm in length) in the tongues of 16 horses, but the authors did not report whether the lower alimentary tract was also affected (Pusterla and others 2006). In the present study, the upper alimentary tract was unaffected by metallic wires of similar length (4 to 8 cm in length) that affected the lower alimentary tract only.…”
Section: Discussionmentioning
confidence: 96%
“…A previous report linked feeding out of cable-framed tractor tyres with metallic foreign body penetration of horses' tongues (Pusterla and others 2006). In the present report, although no specific geographical or management factors could be identified, the authors speculated that metallic wire was inadvertently included as a result of the bailing process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many foreign bodies are radiolucent (ie, wood, hair, or plant material), a contrast fistulogram may provide additional information in the form of a filling defect. 6 Surgical removal of foreign bodies comes with unique challenges because the presence of a foreign body cannot always be confirmed prior to surgery. In our study, foreign body location did not affect the sensitivity of plain film radiography; only metallic foreign bodies were visible regardless of location.…”
Section: Discussionmentioning
confidence: 99%
“…6 An incision is then made along the path of the needle to remove the foreign body. These were readily diagnosed with plain film radiography, so preoperative diagnosis was not as challenging as for nonradiopaque foreign bodies.…”
Section: Discussionmentioning
confidence: 99%